Factors Affecting the Effectiveness and Efficiency of Employees at STMIK Pelita Nusantara - Emmy Hotparsaulian Sirait; John F. Marpaung (Journal of Economics and Business (JECOMBI), 2022)
To enforce discipline, it is not enough just by threats, but it needs balance, namely a sufficient level of welfare. Even so, in fact, discipline is not only determined by the welfare factor, but there are many other factors, it also needs a continuous habit. Based on the preliminary research that has been carried out at STMIK Pelita Nusantara, the problems faced can be formulated as follows "what factors affect the effectiveness and efficiency of employee work at STMIK Pelita Nusantara", while the hypothesis of the problem is as follows: and employee work efficiency is discipline. "Discipline is an absolute requirement for employees of STMIK Pelita Nusantara, among others: To: comply with all official regulations and instructions from superiors in an orderly, precise and perfect manner. Enforcing a good workforce life. Employees are required to fill in the attendance list 2 (two ) times namely when coming and going home.